2018
DOI: 10.1002/adma.201802497
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Control over Hydrogen Bond Formation and Reaction Rates for Scalable Synthesis of Highly Crystalline vdW MOF Nanosheets with Large Aspect Ratio

Abstract: Large‐scale synthesis of van der Waals (vdW) metal–organic framework (MOF) nanosheets with controlled crystallinity and interlayer coupling strength is one of the bottlenecks in 2D materials that has limited its successful transition to large‐scale applications. Here, scalable synthesis of mBDC (m = Zn and Cu) 2D MOFs at large scales through a biphase method is demonstrated. The results show replacing water molecules with pyridine eliminates hydrogen bond formation at metal cluster sites. This prohibits tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…Our results show that the addition of pyridine agent in the upper phase (mixed with metal cations) is effective in producing highly lamellar MnBDC (Figure a,b). The termination effect of pyridine is consistent with our previous report …”
Section: Figuresupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that the addition of pyridine agent in the upper phase (mixed with metal cations) is effective in producing highly lamellar MnBDC (Figure a,b). The termination effect of pyridine is consistent with our previous report …”
Section: Figuresupporting
confidence: 93%
“…Excited by incident laser with a wavelength of 488 nm, obtained lamellar MnBDC crystal shows four dominant Raman peaks (P 1 –P 4 ) in the range of 700 cm −1 to 1700 cm −1 , which are assigned as the vibrations of metal cluster breathing, benzene ring breathing, metal cluster contracting, and benzene ring breathing, respectively . These Raman features collected by attained lamellar MnBDC precisely match with previous results collected from other vdW 2D MOFs containing Zn or Cu metal atoms . Notably, we found that these four featured peaks in lamellar MnBDC uniformly show their full‐width at half‐maximum (FWHM) as narrow as 6.1–6.8 cm −1 .…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we applied Raman vibration to depict the unit cell structure of lamellar MnBDC (Figure d). Excited by incident laser with a wavelength of 488 nm, obtained lamellar MnBDC crystal shows four dominant Raman peaks (P 1 –P 4 ) in the range of 700 cm −1 to 1700 cm −1 , which are assigned as the vibrations of metal cluster breathing, benzene ring breathing, metal cluster contracting, and benzene ring breathing, respectively . These Raman features collected by attained lamellar MnBDC precisely match with previous results collected from other vdW 2D MOFs containing Zn or Cu metal atoms .…”
Section: Figuresupporting
confidence: 87%
“…As the starting point of all the subsequent steps, the acquisition of quality building blocks is imperative yet challenging. This is contingent on proper synthesis of bulk materials, and their exfoliation into dispersible, monolayered and defect‐free 2D nanosheets for membrane fabrication . On this basis, efficient surface modification methods should be available for the nanosheets so that desirable transporting characteristics can be obtained in resultant laminates .…”
Section: Discussionmentioning
confidence: 99%